Bahasa, Seksualitas, dan Identitas Perempuan Dalam Novel “Nyai Gowok Kama Sutra Dari Jawa” Karya Budi Sarjono - T, Tuminih (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study explores the representation of language, sexuality, and female identity in the novel Nyai Gowok, a controversial literary work that holds multiple cultural as well as social meanings. The main focus of this study is how the main female character Nyai Gowok constructs her identity through the use of language and sexuality in the context of Javanese patriarchal culture. The methods applied are critical discourse analysis as well as post-structuralist feminist theory, which allows for understanding the relationships of power, resistance, and agency in the stories of female characters. Analysis findings reveal that Nyai Gowok uses sexuality not just as a tool to serve men, but rather as a strategy of power and a way to assert her identity. The language found in the novel also reveals the ambivalence between subjugation and empowerment, reflecting the complexity of women’s position within the dominant social structure. Thus, Nyai Gowok becomes not only a symbol of repressed femininity, but also a figure capable of negotiating her space and meaning through body, speech, and action.